Model Pembelajaran Membaca Menulis Menghitung (Calistung) pada Anak Usia Dini Di Kabupaten Pekalongan - Istiyani, Dwi (Jurnal Penelitian, 2013)
The focus of this research is the widespread phenomenon of learning to read, write and count in early childhood around the District of Wiradesa, Pekalongan. Why such a phenomenon appears? How the model of learning to read, write and count in early childhood around the District of Wiradesa, Pekalongan? And how it impacts their ability to read, write and count and their psychological. To answer these questions, observation, in-depth interview and documentation were used in this study. To analysis data, review and reflection, exploration, and reduction were used. The results showed that the phenomenon of learning to read, write and count in early childhood in Pekalongan appeared on concerns of parents with a basic level of selection into the elementary school. Many early childhood activities were included in the part-time formal learning. Most of them also followed that lesson in educational institutions. Consequently, those who were following the course outside their formal school mastered faster, although their psychological impact tended to quickly become bored with learning. Meanwhile, the introduction of learning to read, write and count in early childhood in kindergarten was slower because it did not focus solely on that learning, but dominantly in play activities. On the one hand, the kids did not get bored and did not realize they were learning to read, write and count, because learning is integrated in play activities.